Endemic norovirus infections in children, Ho Chi Minh City, Vietnam, 2009-2010. - My, P; Thompson, C; Phuc, H; Tuyet, P; Vinh, H; Hoang, N; Minh, P; Vinh, N; Thuy, C; Nga, T; Hau, N; Campbell, J; et al. (2013)
We performed a case-control investigation to identify risk factors for norovirus infections among children in Vietnam. Of samples from 1,419 children who had diarrhea and 609 who were asymptomatic, 20.6% and 2.8%, respectively, were norovirus positive. Risk factors included residential crowding and symptomatic contacts, indicating person-to-person transmission of norovirus.